Multiple facets in the control of acromegaly (2014)
Aims The current article provides a brief overview of the criteria for defining disease control in acromegaly. Methods This was a retrospective, narrative review of previously published evidence chosen at the author’s discretion along with an illustrative case study from Latin America. Findings and Conclusions In the strictest sense, “cure” in acromegaly is defined as complete restoration of normal pulsatile growth hormone secretion, although this is rarely achieved. Rather than “cure”, as such, it is more appropriate to refer to disease control and remission, which is defined mainly in terms of specific biochemical targets (for growth hormone and insulin-like growth factor-1) that predict or correlate with symptoms, comorbidities and mortality. However, optimal management of acromegaly goes beyond biochemical control to include control of tumour growth (which may be independent of biochemical control) and comprehensive management of the symptoms and comorbidities typically associated with the disease, as these may not be adequately managed with acromegaly-specific therapy alone.